Protein C anticoagulant system—anti-inflammatory effects - Esmon, Charles T. (Seminars in immunopathology, 2012)
Activated protein C (APC) plays active roles in preventing progression of a number of disease processes. These include thrombosis due to its direct anticoagulant activity which is likely augmented by its cytoprotective activity, thereby limiting exposure of procoagulant cellular membrane surfaces on cells. Beyond that, the pathway signals the cells to prevent apoptosis, to dampen inflammation, to increase endothelial barrier function, and to selectively downregulate some genes implicated in disease progression. Most of these functions are manifested to APC binding to endothelial protein C receptor (EPCR) allowing PAR1 activation, but activation of other PARS is also implicated in some cases. In addition to EPCR orchestrating these changes, CD11b is also capable of supporting APC signaling. Selective control of these pathways offers potential in new therapeutic approaches to disease.